2016
DOI: 10.3389/fpsyg.2016.00450
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of Shape and Label in the Misleading Packaging of Food Imitating Products: From Empirical Evidence to Policy Recommendation

Abstract: Food imitating products are chemical consumer items used frequently in the household for cleaning and personal hygiene (e.g., bleach, soap, and shampoo), which resemble food products. Their containers replicate elements of food package design such as possessing a shape close in style to drinking product containers or bearing labels that depict colorful fruits. In marketing, these incongruent forms are designed to increase the appeal of functional products, leading to chemical consumer product embellishment. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…The general pattern of results suggests toddlers do not demonstrate a strong preference to interact with smaller or with larger capsules; across all studies and trials, we found a consistent pattern of no differences in their preferences or selections. Previous research on child poisoning risk suggests young children interact with different household products at different rates, depending on factors such as the shape, labelling, and transparency of those products and the containers holding them [17][18][19][20][21][22]. Research focused on laundry detergent capsules in an ecologically valid setting similar to that used in the present study offers indication that toddlers do not show preference in grasping choice between an assortment of coloured and multi-coloured capsules [25].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The general pattern of results suggests toddlers do not demonstrate a strong preference to interact with smaller or with larger capsules; across all studies and trials, we found a consistent pattern of no differences in their preferences or selections. Previous research on child poisoning risk suggests young children interact with different household products at different rates, depending on factors such as the shape, labelling, and transparency of those products and the containers holding them [17][18][19][20][21][22]. Research focused on laundry detergent capsules in an ecologically valid setting similar to that used in the present study offers indication that toddlers do not show preference in grasping choice between an assortment of coloured and multi-coloured capsules [25].…”
Section: Discussionmentioning
confidence: 61%
“…Previous research on child poisoning risk suggests young children interact with different household products at different rates, depending on factors such as the shape, labelling, and transparency of those products and the containers holding them [ 17 22 ]. Research focused on laundry detergent capsules in an ecologically valid setting similar to that used in the present study offers indication that toddlers do not show preference in grasping choice between an assortment of coloured and multi-coloured capsules [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main objective of this study was to determine the degree of effectiveness of the packaging of an educational toy with the target audience and the sensations and emotions caused by the consumer (target) in the purchasing process ( Fugate, 2008 ). This study has revealed the suggested buying and consumption habits ( Calvert and Brammer, 2012 ) of educational toys, the most valued aspects in the consumption of educational toys, levels of brand and product recall, perception of brand and product value through packaging ( Underwood and Ozanne, 1998 ), projection on the entertainment of toys from packaging ( Basso et al, 2016 ) (design, size, shape, color, touch, etc.). It has also allowed the authors to compare the perception/coding of each container by men and women, identify the level of visual attraction (dedicated times) toward the product and the brand for the two packaging shown (average exposure times in the areas of interest, route, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…However, children will encounter household chemicals eventually and interact with them (Schwebel et al, 2014). Parents do not always adapt their safety measures to their child's increasing mobility or behavior (Gibbs et al, 2005;Schwebel et al, 2006), or their storage decision of household chemicals is misguided by unfamiliarity with safety labels or misinterpretation of other packaging attributes (Basso et al, 2016;Bearth et al, 2017;Bearth & Siegrist, 2019;Buchmüller et al, 2020). Prior studies have specifically addressed the issue of product attributes and their effects on children's perception and behavior (e.g., Schneider, 1977;Schwebel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%